2020
DOI: 10.21005/asp.2020.19.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Wheat, Triticale, Barley and Oat Grains

Abstract: Cereals are the main source of carbohydrates in the human diet, providing the major source of energy and contributing significantly to protein intake. Cereals make up the bigger part of crop production. The chemical composition of cereals depends on agrotechnical factors that affect the quality of grain. Naked oat has the highest protein content. The analysis of crude fat in the grain revealed that the highest values were identified for naked oat and the lowest -in the triticale. The study showed the differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 50 publications
5
49
1
Order By: Relevance
“…Piergiovanni et al [40] also showed higher concentration of calcium in emmer wheat (42.2 mg/kg) than wheat (35 mg/kg). Moreover, Biel et al [37] also reported lower calcium concentrations reported in oats (13.1 mg/kg), wheat (3.7 mg/kg), and barley (4 mg/kg) compared to the present study. erefore, the results of our study demonstrated that emmer wheat can be considered as a good source of calcium than wheat and oats.…”
Section: Mineral Composition Of Emmer Wheatcontrasting
confidence: 54%
See 2 more Smart Citations
“…Piergiovanni et al [40] also showed higher concentration of calcium in emmer wheat (42.2 mg/kg) than wheat (35 mg/kg). Moreover, Biel et al [37] also reported lower calcium concentrations reported in oats (13.1 mg/kg), wheat (3.7 mg/kg), and barley (4 mg/kg) compared to the present study. erefore, the results of our study demonstrated that emmer wheat can be considered as a good source of calcium than wheat and oats.…”
Section: Mineral Composition Of Emmer Wheatcontrasting
confidence: 54%
“…Similarly, earlier reports showed differences in ash content among different emmer (0.85% and 2.46%) varieties [3] and significant effect of growing season on ash content [31]. Biel et al [37] reported that the ash content in common wheat grains and triticale is 1.82% and 1.3%, respectively, which is lower than emmer wheat varieties studied. Jocelyne et al [34] also reported that the ash contents of wheat, maize, sorghum, and millet were 1.41%, 1.79%, 4.16%, and 2.16%, respectively.…”
Section: Crude Fiber Contentmentioning
confidence: 56%
See 1 more Smart Citation
“…of crude fiber, 60 g kg −1 d.m. of nitrogen-free extract [8][9][10]. The biological value of oat protein is not high, but it contains many valuable amino acids, such as lysine and arginine [10].…”
Section: Introductionmentioning
confidence: 99%
“…of nitrogen-free extract [8][9][10]. The biological value of oat protein is not high, but it contains many valuable amino acids, such as lysine and arginine [10]. Of all cereals, oats have the most fiber, mainly in their husks, which Agriculture 2021, 11, 79 2 of 21 reduces their digestibility and energy value [11,12].…”
Section: Introductionmentioning
confidence: 99%